Fuzzy entropy of distinguishing air traffic control students risk level during horizontal flight norms violation - Борсук, С. П. (Problems of Informatization and Control, 2015)
The question of air traffic controller efficient training is always urgent taking into account importanceof their professional education for the flight safety. Traffic controller level estimation is defined withhelp of set of control means that contain group destined for checking his compliance of horizontalplane flight norms. Traffic controller’s attitude about these norms usually is nor checked that leads toorigin of potentially dangerous bifurcation point in case of unpredicted event during the flight. Suchattitude is found with help of fuzzy models, presented as family of membership functions ofcorrespondent linguistic variable with 7-ranks. Fuzzy entropy was used to measure adequacy of suchscale usage. It was found that most notable are best and worst grades that is considered to bemotivation for their reach/avoidance